Clinicoetiological profile and outcomes of acute poisoning in children: experience in a tertiary care centre in North India - Tandon, Aryan; Arya, Arun K. (International Journal of Contemporary Pediatrics, 2025)
Background: Pediatric poisoning is one of the most commonly presenting emergencies. Children due to their playful and inquisitive nature consume substances that are harmful to them unintentionally. Poisoning is also seen with the ideation of self-harm. Understanding the etiology and clinical profile of the commonly consumed poisons in children will help in proper management. Aims and objectives were to study the clinical profile and outcome of children presenting with poisoning in a tertiary care hospital. Methods: This prospective observational study was conducted over a span of 18 months including 211 patients. Appropriate statistical tests were applied and the results were extracted. Results: Accidental poisoning (86.3%) was more frequently observed in males (50.7%), whereas intentional poisoning (13.7%) was more common in adolescent girls (p value=0.007). Longer durations before admission were associated with higher mortality rates (p value <0.0001). Household products (24.6%) were the leading cause of poisoning in children followed by organophosphate poisoning (22.3%), pharmacological drug intake (19%), corrosive intake (12.3%), Celphos poisoning (11.4%), food poisoning (3.8%), plant-based poisoning (3.8%) and rat poison intake (2.8%). Overall, out of the 211 cases, 197 (93%) patients were discharged with follow up advice, while 14 (7%) unfortunately succumbed to their death. Conclusions: Spreading awareness in the community, educating children and their parents, keeping harmful substances away from children, ensuring mental well-being of adolescents, prompt treatment as per protocol and timely referral to a health center where adequate facilities are available will drastically improve the outcome and significantly reduce morbidity and mortality.